2023
DOI: 10.3390/ijms241814342
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Antibody-Mediated Hydrolysis Sites of Oligopeptides Corresponding to the SARS-CoV-2 S-Protein by MALDI-TOF Mass Spectrometry

Anna M. Timofeeva,
Sergey E. Sedykh,
Pavel S. Dmitrenok
et al.

Abstract: Antibodies recognizing RBD and the S-protein have been previously demonstrated to be formed in humans after SARS-CoV-2 infection and vaccination with the Sputnik V adenovirus vaccine. These antibodies were found to be active when hydrolyzing FITC-labeled oligopeptides corresponding to linear epitopes of the S-protein. The thin-layer chromatography method allows the relative accumulation of the reaction product to be estimated but cannot identify hydrolysis sites. This study used the MALDI-TOF MS method to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Another fundamental issue is the analysis of antibody-mediated hydrolysis sites. Previously, we conducted a MALDI-TOF analysis of the hydrolysis sites of S-protein-related oligopeptides with antibodies isolated from the blood plasma of patients who have recovered from COVID-19 [28]. It has been shown that catalytic antibodies hydrolyze peptide bonds, but the observed type of proteolysis was not similar to that of proteolytic enzymes, such as trypsin and chymotrypsin.…”
Section: Discussionmentioning
confidence: 99%
“…Another fundamental issue is the analysis of antibody-mediated hydrolysis sites. Previously, we conducted a MALDI-TOF analysis of the hydrolysis sites of S-protein-related oligopeptides with antibodies isolated from the blood plasma of patients who have recovered from COVID-19 [28]. It has been shown that catalytic antibodies hydrolyze peptide bonds, but the observed type of proteolysis was not similar to that of proteolytic enzymes, such as trypsin and chymotrypsin.…”
Section: Discussionmentioning
confidence: 99%